Pendampingan Melalui Program Pembinaan Kompetisi Sains Madrasah Sebagai Upaya Peningkatan Prestasi - Eny Latifah; Yusuf Yusuf (Jurnal Kabar Masyarakat, 2025)
This Community Service has the objective of providing assistance to students at the Elementary Madrasah level in the Republic of Indonesia Ministry of Religion Program called the Madrasah Science Competition (KSM). As a form of community service in improving student achievement, there needs to be guidance in encouraging the existing KSM program. The purpose of the service is to provide guidance for elementary Madrasah students in KSM in the fields of Science and Mathematics Integration of Religion. The results of community service are (1) Guidance is given in the form of providing materials, trials and evaluations; (2) Guidance in the form of assistance in providing motivation and direction in participating in KSM; and (3) Guidance can provide a positive impact, especially for students who participate in KSM and Educational Institutions in general in improving the quality of education. (4) Guidance is able to improve student achievement in the field of science that is of interest in the competition.